Long-term outcome of radiotherapy-induced taste dysfunction in head and neck cancer patients: A pilot study - Marc Guedea; Andrea Parra; Helena Viñals; Sonia Almendros; Inés Guix; Isabel Linares; Montse Ventura; Lluis Giner; Ferran Guedea; Alicia Lozano (Journal of Dental Problems and Solutions - Peertechz Publications, 2020)
Aims: Taste dysfunction is a frequent complaint in head and neck cancer patients treated with Radiation Therapy (RT), which impairs nutritional support and affects quality of life. A prospective unicenter pilot study was conducted to assess taste dysfunction of the four basic tastes (sweet, salty, bitter, sour) and umami in four patients receiving RT for head and neck cancer. Methods: In four male patients (mean age 56 years) diagnosed with squamous cell carcinoma of the larynx (n= 2) and hypopharynx (n= 1) and undifferentiated carcinoma of the nasopharynx (n= 1), Volumetric Modulated Arc Therapy (VMAT) was administered with a total dose of 69,9 Gy on the tumor (2,12 Gy per fraction) and 54,12 Gy on risk lymph node areas at risk of suclinical disease (1,64 Gy per fraction), five times each week for 7 weeks. Cisplatin chemotherapy was administered for 3 cycles (every 21 days). The filter-paper disc was used to assess thresholds of sweet, salty, bitter, sour tastes, and the whole-mouth taste method for umami. Testing was performed before RT, at 3 weeks (during RT), at 6 weeks (during RT), at 12 months (after RT) and at 14 months (after RT).   Results: The four basic tastes experienced a decrease in their recognition threshold at 3 and 6 weeks as compared with pre-RT values, but at 12 and 14 months values were similar to those before treatment. The perception of the umami taste follows a pattern similar to the four basic tastes and normalized from the year of starting radiotherapy. Conclusion: In the long-term, pilot study, the four basic tastes and umami declined during the first 6 weeks after the start of RT but improved up to pre-treatment values after a follow-up of 14 months. Restoration of test abilities is clinically relevant for head and neck cancer patients treated with RT.